COVID-19Pneumonia and its Mortality rates in Afghanistan; A Cross-sectional Study 2021-2022 - Razia Miri; Sughra Alizada; Zahra Alizada; Zahra Shafaee; Abdullah Rezaie (Genius Journals, 2023)
Corona virus is considered one of the dangerous viruses of the last decade, which has caused challenges to human life in different dimensions with its rapid spread. This virus causes an increase in the number of deaths among patients by causing pneumonia. Aim and method: The aim of this study is to investigate the mortality rates of covid-19 patients with pneumonia, the required data of which was collected from the AfghanJapan hospital in six months between 2021 and 2022. Results: In this study, information was collected from 229 patients with COVID-19 pneumonia, of which 135 patients recovered but 94 patients died. Although the majority of variables studied in this research are similar between deceased and recovered patients, the blood oxygen level and breathing rate of deceased and recovered patients are different. Conclusion: The presence of pneumonia in patients with COVID-19 causes the deterioration of the patient's condition and even causes the patient's death.
Keywords: Pneumonia COVID-19; Mortality rates and Kabul